Service Quality, Customer Satisfaction and Behavioural Intentions in the Banking industry: the case of Middle East - Sangeetha, Jaya (Archives of Business Research, 2018)
The link between Service Quality, Customer Satisfaction and Behavioural Intentions has been of interest to academicians and practitioners alike considering their potential to contribute to the effectiveness and success of the organization. This study endeavours to establish the nature of link between the three constructs in the Middle Eastern country and culture context, using a customized measurement tool developed for this unique context. Using cluster sampling method involving 373 retail banking customers of the major commercial banks in Oman, the study reveals that in the retail banking environment, Service Quality contributes to Customer Satisfaction and the link is strong and significant. Customer Satisfaction is found to lead to Behavioural Intentions but the link is weak but significant. Guidelines are provided for practicing managers for formulating strategies to leverage and strengthen the relationships.